Urgensi Perkuat Layanan Bimbingan dan Konseling pada Masa Transisi Siswa SMP - Nafisah, Durrotun; Hamida, Amaliah; Habsy, Bakhrudin All (Lembaga Yasin AlSys, 2024)
Junior High School or mostly called SMP, is often referred to as a transitional period. During this time, students often face challenges and difficulties that require guidance and counseling services to help them navigate this crucial stage. However, limited access to guidance and counseling services prevents students from receiving optimal support. This can lead to various problems, including unaddressed student issues, declining academic performance, and impaired mental health. Therefore, strategic steps are needed to strengthen guidance and counseling services in SMP.This study employs a qualitative library research method. Based on data analysis, it is concluded that guidance and counseling in SMP need to be strengthened to ensure optimal delivery of services. The following are strategic steps for strengthening guidance and counseling services in SMP: (1) Increasing the number of guidance and counseling teachers. (2)Enhancing the professionalism of guidance and counseling teachers. (3)Developing infrastructure and resources. (4)Implementing a comprehensive and systematic guidance and counseling program. (5)Establishing collaboration with internal and external stakeholders of the school. It is expected that by strengthening these services, guidance and counseling can be effectively delivered, creating a conducive learning environment, and supporting holistic student development.